If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+(3x+11)=3
We simplify the equation to the form, which is simple to understand
x+(3x+11)=3
Remove unnecessary parentheses
+x+3x+11=+3
We move all terms containing x to the left and all other terms to the right.
+1x+3x=+3-11
We simplify left and right side of the equation.
+4x=-8
We divide both sides of the equation by 4 to get x.
x=-2
| (11x-1)+(5y-5)=180 | | -12x+8y=-12 | | -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 | | 4=m/7+5 | | 5n=-3n | | v^3=37 | | 4(x-4)+8=12 | | 2(x+4)+3=15 | | 55=x-48 | | 3x-2=8x-1 | | 6.43-10d=2.5 | | -2c+5=-c+2 | | 9x+15=14x-11 | | 2a-17+20a-9= | | -2(2k-4)=4(k-2) | | 8-5(2-x)=5+3(x-4) |